2018
DOI: 10.1007/82_2018_83
|View full text |Cite
|
Sign up to set email alerts
|

Niche Construction and Exploitation by Agrobacterium: How to Survive and Face Competition in Soil and Plant Habitats

Abstract: Agrobacterium populations live in different habitats (bare soil, rhizosphere, host plants), and hence face different environmental constraints. They have evolved the capacity to exploit diverse resources and to escape plant defense and competition from other microbiota. By modifying the genome of their host, Agrobacterium populations exhibit the remarkable ability to construct and exploit the ecological niche of the plant tumors that they incite. This niche is characterized by the accumulation of specific, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 208 publications
0
24
0
1
Order By: Relevance
“…Opines produced in tumors therefore serve as a selective nutrient source for tumorigenic bacterium and induce conjugative transfer of Ti plasmids (reviewed in Dessaux et al. 1998; Farrand 1998; Dessaux and Faure 2018a). On the other hand, our results suggested that the strain Colt5.8 is also able to catabolize opines and exploit crown gall tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opines produced in tumors therefore serve as a selective nutrient source for tumorigenic bacterium and induce conjugative transfer of Ti plasmids (reviewed in Dessaux et al. 1998; Farrand 1998; Dessaux and Faure 2018a). On the other hand, our results suggested that the strain Colt5.8 is also able to catabolize opines and exploit crown gall tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Opines are specific organic compounds that are mainly used as selective nutrient sources by a pathogen (Dessaux et al. 1998; Dessaux and Faure 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic agrobacteria can catabolize opines using genes carried by their Ti plasmid. Opines are mainly used as carbon and nitrogen sources, but can also be used as phosphate or sulfur sources (Dessaux et al, 1998; Flores-Mireles et al, 2012; Dessaux and Faure, 2018). One of the features of the Ti plasmid is that it confers the bacterium that harbors it the possibility to catabolize a specific type of opine determined by the Ti plasmid-type (Gordon and Christie, 2014).…”
Section: Bacteria Find Trophic Resources and Toxic Compounds Inside Tmentioning
confidence: 99%
“…Around 40 different types of opines have been characterized; some of them trigger the transfer of the Ti plasmid from one bacterium to another, enhancing pathogenicity and contributing to the persistence of pathogenic bacteria in the environment (Dessaux et al, 1998; Flores-Mireles et al, 2012). These properties confer opines a central role in the Agrobacterium -infected plant interaction (Guyon et al, 1980; Dessaux and Faure, 2018). According to the “opine concept,” the presence of opines improves the competitiveness of the bacteria able to catabolize them at the expense of the bacteria unable to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizobiaceae is a family of bacteria that include soil-dwelling and plant associated bacteria. integrates into the plant chromosomes (1)(2)(3)(6)(7)(8)(9)(10)(11). The T-DNA segment encodes for metabolic and hormone-producing enzymes that hijack the plant to produce custom energy sources that only Agrobacterium can use (9,10).…”
Section: Introductionmentioning
confidence: 99%